Women in Teacher Leadership - Branton, Olivia (East Carolina University)
This study examined the impacts of women teacher leaders on shaping instruction and collaboration across K-6 educational contexts in the United States. Utilizing a survey method, I gathered data through Likert-type and open-ended questions to explore how women teacher leaders shape collaboration and instruction. Researcher-developed tools were shared via social media and email to encourage broad outreach, though exact participant location data was not collected. Quantitative and qualitative data were analyzed to identify leadership characteristics, strategies, and their perceived influence on instructional practices. This research aimed to provide insights into the unique contributions of women teacher leaders and inform leadership development practices and policies within diverse educational environments. Quantitative findings suggested that leadership behaviors were generally consistent across demographics, while qualitative analysis revealed key themes of mentorship, modeling, inclusive leadership, and relationship building. These findings highlight the importance of empowering women teacher leaders through professional development that shows value to collaboration and reflective practices. By emphasizing the voices of educators, the study contributed to a deeper understanding of gender dynamics in teacher leadership, with implications for district-wide student success.
Keywords: Education, Elementary; Education, General